SAFEHEART risk-equation and cholesterol-year-score are powerful predictors of cardiovascular events in French patients with familial hypercholesterolemia. (August 2020) - Gallo, Antonio; Charriere, Sybil; Vimont, Alexandre; Chapman, M. John; Angoulvant, Denis; Boccara, Franck; Cariou, Bertrand; Carreau, Valérie; Carrié, Alain; Bruckert, Eric; Béliard, Sophie; ,; et al.
Abstract: Background and aims: Patients with heterozygous familial hypercholesterolemia (HeFH) present elevated cardiovascular (CV) risk. Current CV risk stratification algorithms developed for the general population are not adapted for heFH patients. It is therefore of singular importance to develop and validate CV prediction tools, which are dedicated to the HeFH population. Methods: Our first objective was to validate the Spanish SAFEHEART-risk equation (RE) in the French HeFH cohort (REFERCHOL), and the second to compare SAFEHEART-RE with the low-density-lipoprotein-cholesterol (LDL-C)-year-score for the prediction of CV events in the HeFH French population. Results: We included HeFH (n = 1473) patients with a genetic or clinical diagnosis (DLCN score ≥8). Among them, 512 patients with a 5-year follow-up were included to validate the 5 year-CV-RE. A total of 152 events (10.3%) occurred in the entire population of 1473 patients during a mean follow-up of 3.9 years. Over the five-year follow-up, non-fatal CV events occurred in 103 patients (20.2%). Almost all the parameters used in the SAFEHEART-RE were confirmed as strong predictors of CV events in the REFERCHOL cohort. The C-statistic revealed a satisfactory performance of both the SAFEHEART-RE and LDL-C-year-scores in predicting CV events for all the patients (primary and secondary prevention) (C-index 0.77 and 0.70, respectively) as well as for those in primary prevention at inclusion (C-index 0.78 and 0.77, respectively). Conclusions: This analysis represents the first external validation of the SAFEHEART-RE and demonstrated that both SAFEHEART-RE and the LDL-C-year-score are good predictors of CV events in primary prevention HeFH patients. Graphical abstract: SAFEHEART-RE and LDL-C-year score are good predictors of CV events in patients with heterozygous Familial Hypercholesterolemia in primary prevention (left ROC curves) and in primary and secondary prevention (right ROC curves). Image 1 Highlights: SAFEHEART-risk equation can now be used in other European population of HeFH patients to predict CV events. The cholesterol-year-score is a robust predictor of CV events in HeFH patients. SAFEHEART-RE and the cholesterol-year-score are valid in primary prevention heFH patients.